Study the Effect of Arabidopsis thaliana Extract on Reducing Blood Glucose Level in Diabetic White Albino Mice - I. Rashid, Khaleel; M. Aljibouri, Abedaljasim; J. Zayer, AbdulAmeer; B. Khalid, Luma; Abdul-Munaem, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2017)
This study was designed to evaluate the effect of aqueous extract of Arabidopsis thaliana seeds on reducing glucose level for white albino mice. Twenty adults mice were used, divided randomly into four groups (five mice per each group). The first group (normal mice) was administrated with 0.1 ml of distilled water as a control, the second group (normal mice) was administrated with 0.1 ml of the plant extract, whereas the third and fourth groups (diabetic mice) were administrated with single dose of alloxan (150 mg/kg of the body weight) to induce diabetes, and the fourth group was administrated with 0.1 ml of the plant extract for 10 days, then blood glucose level was measured for all of the experimental animals (diabetic and non diabetic). Results showed clear increasing in glucose levels in the diabetic mice, while significant reduction was recorded in glucose levels of the normal mice that was treated with the plant extract as compared with the control group. These results indicate that Arabidopsis thaliana seeds aqueous extract possesses a hypoglycemic effect. Key words: Arabidopsis thaliana, glucose level, albino mice